Hubungan Pola Asuh Orang Tua Terhadap Perkembangan Sosial Anak Di Tk Lazuardi Kamila Global Islamic School Surakarta Tahun 2015/2016 - Anindya, Destiara (2016)
Early Childhood Education (ECD) is a development effort aimed at children from birth to the age of 6 (six) years which is done through the provision of educational stimulus to assist the growth and development of the physical and spiritual child to have readiness in entering further education. This study aimed to identify the relationship parenting parents on social development of children in kindergarten Lazuardi Kamila Global Islamic School Surakarta 2015/2016 and find out how much parenting parents relationship to the social development of children in kindergarten Lazuardi Kamila Global Islamic School Surakarta 2015/2016. This research uses descriptive quantitative research. This study was conducted in kindergarten Lazuardi Kamila Surakarta Global Islamic School for kindergarten groups A and B at the kindergarten school year 2015- 2016. The research sample as many as 73 children from kindergarten A kindergarten and kindergarten in Lazuardi Kamila Global Islamic School Surakarta as many as 49 children in a kindergarten, and 24 children in kindergarten B. Sampling using simple random sampling. Collecting data using questionnaires. Hypothesis testing used product moment correlation analysis.Based on the analysis that there is a relationship between parenting parents permissive towards social development of children in kindergarten Lazuardi Kamila Surakarta Global Islamic School Year 2015/2016. This is evidenced by the results of perarson correlation r value of -0.325 with a significance of 0.005 <0.01 (p = 0.005; p <0.01), which means Ho is rejected, which means that there is a relationship between permissive parenting parents with children in social development kindergarten in Lazuardi Kamila Surakarta Global Islamic School Year 2015/2016.